Hypertension is associated with antibody response and breakthrough infection in health care workers following vaccination with inactivated SARS-CoV-2 - Soegiarto, Gatot; Wulandari, Laksmi; Purnomosari, Dewajani; Fahmita, Karin Dhia; Gautama, Hendra Ikhwan; Hadmoko, Satrio Tri; Prasetyo, Muhammad Edwin; Mahdi, Bagus Aulia; Arafah, Nur; Prasetyaningtyas, Dewi; Negoro, Pujo Prawiro; Prakoeswa, Cita Rosita Sigit; et al. (Elsevier Ltd, 2022)
Several types of vaccines have been developed to prevent the coronavirus disease 2019 (COVID-19). It is important to understand whether demographic and clinical variables affect the effectiveness of various types of vaccines. This study analysed the association between demographic/clinical factors, antibody response and vaccine effectiveness in healthcare workers vaccinated with inactivated virus. We enrolled 101 healthcare workers who received two doses of inactivated viral vaccine (CoronaVac). Blood samples were analysed at 1, 3, and 5 months after the second dose of vaccination. Data regarding demographic characteristics, medical histories, and clinical parameters were collected by interview and medical examination. In a separate retrospective study, we analysed the incidence of vaccine breakthrough infection on 2714 healthcare workers who received two doses of inactivated viral vaccine. Medical histories and demographic data were collected using a structured self-reported questionnaire. We found that antibody titres markedly increased at 1 month after vaccination but gradually decreased at 3–5 months post-vaccination. We observed a significant association between age (≥40 years) and antibody level, whereas sex and body mass index (BMI) exhibited no effect on antibody titres. Amongst clinical variables analysed, high blood pressure and history of hypertension were significantly correlated with lower antibody titres. Consistently, we found a significant association in the retrospective study between hypertension and the incidence of breakthrough infection. In conclusion, our results showed that hypertension is associated with lower antibody titres and breakthrough infection following COVID-19 vaccination. Thus, blood pressure control might be important to improve the efficacy of inactivated virus vaccine.